Laser Marking Methods (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Different methods for laser marking are systematized and discussed in the paper. Today in the practice there are many different methods that could be used to realise high quality on the workpiece of various materials with various shapes. Some materials could be marked only by marking or engraving without special requirements and difficulty, while for other materials one can choose the concrete method about the kind of material, marking type, and the specific needs of the production process and the geometry of detail. This makes it necessary to know, to summarise and systematize in a database all methods for particular lasers and materials, in order to quickly and flexibly respond to the specific needs of each customer by the manufacturies on marking systems. The report studies the specific opportunities and fields of applications of different methods for marking with laser.